The effects of drought stress on the photosynthetic processes of wheat and of Aegilops biuncialis genotypes originating from various habitats - Molnár, István (Acta Biologica Szegediensis, 2002)
The effects of drought stress, simulated by increasing concentrations of PEG, were examined on the photosynthetic processes of wheat and of Aegilops biuncialis genotypes originating from various habitats. In the course of moderate stress Ae. biuncialis lines originating from dry habitats fixed more CO2 than the wheats due to the less intense stomatal closure. After the greater water loss caused by hard drought stress they had more rapid regeneration ability compared to the wheats. In the case of the wheat variety Sakha drought stress resulted in the induction of the generative phase, with an acceleration in flowering and ripening processes. The properties of Ae. biuncialis lines originating from dry habitats could be suitable for improving the drought tolerance of wheat.